Band gap and work function tailoring of SnO2 for improved transparent conducting ability in photovoltaics. Issue 7 (21st January 2016) - Ganose, Alex M.; Scanlon, David O.
Abstract : Alloying of PbO2 with SnO2 results in a material with a tuneable band gap, larger electron affinity and smaller electron effective mass, whilst maintaining high levels of optical transparency. These properties are expected to give rise to a more efficient transparent conducting oxide for use in photovoltaic applications. Abstract : Transparent conducting oxides (TCOs) are an essential component in modern optoelectronic devices, such as solar panels and touch screens. Their ability to combine transparency and conductivity, two properties that are normally mutually exclusive, have made them the subject of intense research over the last 50 years. SnO2, doped with F or Sb, is a widely used and relatively inexpensive transparent conducting material, however, its electronic structure leaves scope for improving its properties for use in many TCO applications, especially in solar cell devices. Here we show using density functional theory that incorporation of Pb into SnO2 reduces the band gap through lowering of the conduction band minimum, thereby increasing the electron affinity. The electron effective mass at the conduction band minimum decreases alongside the band gap, indicating improved charge carrier mobilities. Furthermore, the calculated optical absorption properties show the alloys retain their transparency in the visible spectrum. Our results suggest that alloying of PbO2 with SnO2 will enable improved electronic properties, including a highly tuneable workfunction, which will open up the material for other applications, such as hole injection layers in organic photovoltaics.